Effect of biochar on Cd and pyrene removal and bacteria communities variations in soils with culturing ryegrass (Lolium perenne L.). (October 2020) - Li, Guirong; Chen, Fukai; Jia, Shengyong; Wang, Zongshuo; Zuo, Qiting; He, Hongmou
Abstract: Organic contaminations and heavy metals in soils cause large harm to human and environment, which could be remedied by planting specific plants. The biochars produced by crop straws could provide substantial benefits as a soil amendment. In the present study, biochars based on wheat, corn, soybean, cotton and eggplant straws were produced. The eggplant straws based biochar (ESBC) represented higher Cd and pyrene adsorption capacity than others, which was probably owing to the higher specific surface area and total pore volume, more functional groups and excellent crystallization. And then, ESBC amendment hybrid Ryegrass ( Lolium perenne L. ) cultivation were investigated to remediate the Cd and pyrene co−contaminated soil. With the leaching amount of 100% (v/w, mL water/g soil) and Cd content of 16.8 mg/kg soil, dosing 3% ESBC (wt%, biochar/soil) could keep 96.2% of the Cd in the 10 cm depth soil layer where the ryegrass root could reach, and it positively help root adsorb contaminations. Compared with the single planting ryegrass, the Cd and pyrene removal efficiencies significantly increased to 22.8% and 76.9% by dosing 3% ESBC, which was mainly related with the increased plant germination of 80% and biomass of 1.29 g after 70 days culture. When the ESBC dosage increased to 5%, more free radicals were injected and the ryegrass germination and biomass decreased to 65% and 0.986 g. Furthermore, when the ESBC was added into the ryegrass culture soil, the proportion of Cd and pyrene degrading bacteria Pseudomonas and Enterobacter significantly increased to 4.46% and 3.85%, which promoted the co−contaminations removal. It is suggested that biochar amendment hybrid ryegrass cultivation would be an effective method to remediate the Cd and pyrene co−contaminated soil. Graphical abstract: Image 1 Highlights: Eggplant straws based biochar showed higher adsorption of soil Cd and pyrene. Biochar kept Cd in upper soil layer where the plant root could reach. Biochar enhanced Ryegrass (Lolium perenne L. ) remediating contaminated soil. More free radicals were injected by dosing excessive biochar. Proportion of Cd and pyrene degrading bacteria in soil were increased by biochar. Abstract : The Cd and pyrene could be efficiently kept in the upper soil layer by eggplant straws based biochar, which positively facilitated the co−contaminants root uptake by ryegrass.